The method of bilingual partial immersion teaching and the method of intensification for the teaching of English in general and specific skills in sixth grade students - Cardich San Juan, Roxana (2017)
The study seeks to determine the effects that two training programs types for foreignlanguage as represented by the partial immersion bilingual program to a program ofbilingual education intensification of a second language have on the development ofstudent cognitive abilities,. The study has been carried out with 130 students in the sixthgrade of elementary school. The results show global differences in the general and specificabilities of the evaluated student with a better performance of the group that studieswith a methodology of intensification. The study distinguishes differences in the areas ofattention and concentration, adaptation, reading accuracy, spelling phonics, arithmeticand mathematical problem solving, standing out comparatively higher scoring studentswho study following a method of intensification. The areas that show no differences arethe reason reading comprehension, reading speed and visual and regulated spelling.The research leads to value the importance of teaching a second language from primaryeducation through the use of communicative methodologies that respect the consolidationof the mother language in learning and encourage the linkage with a second language in autilitarian, practical and experiential way.